(untitled) (The Planet, 2024)
Introduction: Preeclampsia (PE) is a type of pregnancy hypertension that affects 4-5% of women. The illness is distinguished by elevated blood pressure and proteinuria after 20 weeks of gestation. Its complications include a major cause of morbidity and mortality in both the mother and the fetus. The study aimed to determine if there is a significant relationship between Serum CRP levels and fetal outcomes in women with preeclampsia women. Methods and materials: This cross-sectional analytical study was conducted at the Department of Obstetrics and Gynecology at the Institute of Child and Mother Health (ICMH), Matuail, Dhaka. It took place from January to December 2018. Results: The study involved 120 participants evenly distributed across three groups (A, B, and C), predominantly aged 18-25 years, with similar educational and socioeconomic backgrounds. Groups A and B had higher BMIs than C (p<0.05). Fetal birth weight varied significantly (p<0.05) with 23.3% low birth weight in severe preeclampsia, 16.7% in mild preeclampsia, and 5.0% in normal pregnancies. Maternal CRP levels negatively correlated with newborn birth weights (r = -0.470, p < 0.001). Low-birth-weight and IUGR babies had higher CRP proportions (p < 0.001 and p < 0.01, respectively). Conclusion: This study emphasizes the crucial connection between elevated CRP levels in preeclampsia and adverse fetal outcomes such as lower birth weights, prematurity, and IUGR. It underscores the value of monitoring CRP, particularly in preeclampsia cases, to enable early intervention and enhance fetal well-being.